Pengaruh Bahasa Asing terhadap Bahasa Indonesia dan Bahasa Daerah: Peluang atau Ancaman? - I Wayan Pastika, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The Indonesian language has developed very fast in modernizing its vocabulary by taking in many influences from foreign languages including Arabic, Dutch, English, Sanskrit, Tamil and Chinese. Similar tendencies are apparent in local languages, taking vocabulary in limited numbers from limited sources. Balinese, for instance, has taken loan words in classical and traditional religious matters from Sanskrit through Old Javanese and has let itself be influenced almost exclusively by English for modern vocabulary. Meanwhile Indonesian, which originated from Malay, has developed progressively from an early history, such as Sriwijaya kingdom, to becoming a coastal linguafranca across the country and the declaration of the language as the national language. Nowadays the government and educated people do very little to control influence on the language. A careful academic examination in relation to microlinguistic and macrolinguistic systems, cultural identity and nationality should be considered seriously when new foreign words are taken as part of the Indonesian vocabulary. Otherwise, in the long run, the national language will lose its identity and spoken and written Indonesian will be massively shaped by English elements. This kind of tendency has been very widespread in recent years
Keywords: national language; loanwords; English